New Essays in Technical and Scientific Communication: Research, Theory, Practice - Anderson, Paul V (Baywood's technical communications series, 1983)
Represents an important collection of writings about technical communications. Focusing on a range of theoretical and practical issues, this title includes essays which reflect the rigor, vitality, and interdisciplinary nature of modern technical communications.